High Suburban Fertility: Evidence from Four Northern European Countries - Gunnar Andersson; Hill Kulu; Paul J. Boyle (Demographic Research, 2009)
This study examines fertility variation across different residential contexts in four Northern European countries: Denmark, Finland, Norway and Sweden. We move beyond the conventional urban-rural focus of most previous studies of within-nation variations in fertility by distinguishing between urban centres and suburbs of cities and towns. We base our study on aggregate and individual-level register data and our analysis shows that fertility levels are significantly higher in suburbs than in urban centres; this pattern has persisted over the past quarter of a century for all four countries. A parity-specific analysis of Swedish register data reveals that total fertility varies between central cities and suburbs due to the relatively high first- and second-birth propensities in the suburbs. Further analysis shows that fertility variation between the central cities and suburbs persists after controlling for women's socioeconomic characteristics. We discuss the role of various factors in accounting for high suburban fertility including omitted individual characteristics, contextual factors and selective residential moves of couples planning to have a child.